Evaluating the cost utility of racecadotril in addition to oral rehydration solution versus oral rehydration solution alone for children with acute watery diarrhea in four low middle-income countries: Egypt, Morocco, Philippines and Vietnam. (31st December 2022) - Rautenberg, Tamlyn Anne; Downes, Martin; Kiet, Pham Huy Tuan; Ashoush, Nermeen; Dennis, Antonio Rosete; Kim, Kyoo
Abstract: Aim: To evaluate the cost utility of adjunct racecadotril and oral rehydration solution (R + ORS) versus oral rehydration solution (ORS) alone for the treatment of diarrhoea in children under five years with acute watery diarrhoea in four low-middle income countries. Method: A cost utility model, previously developed and independently validated, has been adapted to Egypt, Morocco, Philippines and Vietnam. The model is a decision tree, cohort model programmed in Microsoft Excel. The model structure represents the country-specific clinical pathways. The target population is children under the age of five years presenting with symptoms of acute watery diarrhea to an outpatient clinic or general physician practice. A healthcare payer perspective has been analysed with the model parameterised with local data, where available. Most recent cost data has been used to inform the drug, outpatient and inpatient costs. Uncertainty has been explored with univariate deterministic sensitivity. Results: According to the base case models, R + ORS is dominant (cost-saving, more effective) versus ORS alone in Egypt, Morocco, Philippines and Vietnam. The incremental cost-effectiveness ratios in each country fall in the southeast (cost-saving, more effective) quadrant and represent a cost savings of −304, 152 EGP per QALY gain in Egypt; −6, 561 MAD per QALY gain in Morocco; −428, 612 PHP per QALY gain in Philippines and −113, 985, 734 VND per QALY gain in Vietnam. Univariate deterministic sensitivity analysis shows that the three most influential parameters across all country adaptations are the utility of children without diarrhea; the utility of inpatient children with diarrhea and the cost of one night of inpatient care. Conclusion: In keeping with similar findings in upper-middle and high-income countries, the cost utility of R + ORS versus ORS is favourable in low-middle income countries for the treatment of children under five with acute watery diarrhoea. PLAIN LANGUAGE SUMMARY: Decision-makers rely on cost utility models to inform decisions about whether to publicly fund treatments as part of Universal Health Care. In low-middle income countries, the capacity to prepare cost utility models may be limited and using existing validated models is a practical solution to assist decision making. This study uses a cost utility model developed and independently validated for the United Kingdom, and adapts it to Philippines, Egypt, Morocco and Vietnam. The model evaluates the clinical benefit and economic impact of using racecadotril in addition to rehydration solution to treat diarrhoea in children. The results show that racecadotril is cost-saving and improves the quality of life for children in Philippines, Egypt, Morocco and Vietnam.